Korelasi Tingkat Spiritualitas Dengan Tingkat Stress Pada Klien Diabetes Tipe 2 - Ubaidillah, Zaqqi; Al Husna, Chairul Huda; Ningrum, Winda Widya; Rahayu, Henik Tri; Ruhyanudin, Faqih; Purwanto, Edi; Agustiyaningsih, Titik; Nur Rohmah, Anis Ika (Universitas Tribhuwana Tunggadewi, 2023)
Stress in diabetic patients creates a serious issue with disease severity. Stress can significantly impact an individual's physical, psychological, intellectual, social, and spiritual. In addition, stress becomes a threat to the physiological imbalance. By considering the magnitude consequences of stress on diabetic patients, it is necessary to find a way to manage stress. The research aimed to determine the relationship between spirituality and stress levels in diabetic patients. The correlational design was used and conducted at the Dinoyo Public Health Center using an accidental sampling technique. The number of respondents in this study was 150 diabetic patients, and the sample of the study was calculated using the G*Power application. The questionnaires used to collect data were Multidimensional Measure of Religiousness/Spirituality and Perceived Stress Scale-10. The data was statistically tested using Spearman Rho. The results showed a p-value or significant value (0.000) less than α (0.05), which means there was a relationship between spirituality and stress levels in diabetic patients. In conclusion, the diabetes patients showed a high level of spirituality within low-stress levels on average.